Studio art therapy cultivating the artist identity in the art therapist - Moon, Catherine Hyland (London Jessica Kingsley Publishers, 2002)
This book presents a model of art therapy where the processes of art constitute the core of the model. It addresses how an arts-based approach can inform the therapist in all aspects of practice, from the conception of the work and the attempt to understand client needs to interacting with clients and communicating with others about art therapy.
Includes bibliographical references (pages 311-327) and index.
Keywords: Art therapy